Practice narratives enhance children’s memory reports - Whiting, Brittany F. (2017)
Practicing recall of a non-target event prior to discussing substantive issues is a relatively new recommendation for interviews with child victims and witnesses. Despite evidence of the effectiveness of these practice narratives in obtaining detailed reports from children, specific recommendations about the duration and content of these interviews have yet to be systematically investigated. In the present study, 176 children aged 6-10 years watched a magic show and then participated in an interview that began with a practice narrative, with varying length (2 or 5 minutes) and topics (unique or commonplace), or no practice narrative. Conducting a practice narrative of any kind was beneficial to children's subsequent recall of accurate details over no practice narrative. Benefits to children's accurate recall were observed with as little as 2 minutes of practice and practice narratives were particularly beneficial if a unique, rather than commonplace, experience was targeted for practice recall. The present results confirm previous field research and laboratory findings indicating that the substantive phase of the interview is enhanced by conducting a practice narrative and extends the benefits of practice narratives to even a very brief practice narrative.